Explorando os componentes dos protestos #ENDSARS de 2020 na Nigéria dentro dos esquemas da semiótica social (Revista de Estudos da Linguagem, 2024)
This study examined the semiotic resources of the October 2020 #ENDSARS protests in Nigeria, manifesting the affordances operational in the protests. The investigation beckoned on 13 different communicative semiotic configurations, employing Halliday’s grammatical group rank, to delineate the structures. This paved the way for tables and graphs to account for the written modes’ recurrent components. Kinesics such as proxemics, gestures, and gaze supported the analysis, providing relevant semantic implications to non-verbal elements and body language of protesters. This investigation indicated that #ENDSARS hashtag, functioned in variegated forms, as the initiator of the protest, socializing people even without notable leaders. The texts illustrated the suffering of the people from SARS operatives’ gun-punch coercion, as exemplified in a boy-like image’s head, and the cry of agony illuminated through a gestural movement of mouths and hands. Parallel to that is the metaphorical castigation of an innocent young man, manifested through chained hands. Significantly, the research revealed the collective unanimity of the protesters, demonstrated through clenched fists, epitomizing camaraderie of purpose. The protesters made their call to abrogate SARS operations pleasurably-funny in the appearance of a clown and a sacrificial lamb. Given that the idea of social justice is non-negotiable. Demanding a just course should not lead to brutality; the government should rather respond to the request of protesters to fulfill promises made during electioneering campaigns.